Evaluation of General Anesthesia and Sedation and Follow-Up Compliance in Pediatric Dental Procedures: A Comprehensive Analysis of Long-Term Outcomes and Gender Differences - Maria Sarapultseva; Alexey Sarapultsev (MDPI AG, 2024)
This retrospective study evaluated the effectiveness of different types of general anesthesia (GA) and sedation in pediatric dental procedures, focusing on treatment outcomes and follow-up compliance with an emphasis on gender differences. Clinical records of 1582 pediatric patients, aged 0-18 years, were analyzed to examine the distribution, duration and impact of anesthesia types on dental procedure complexity. The study population was divided into three age groups: 0-6, 7-12 and 13-18 years. We assessed follow-up attendance rates by gender and anesthesia type, calculated the decayed, missing and filled (DMF) index and evaluated the need for further treatment and reasons for retreatment. Our findings indicated that general anesthesia with inhalational agents and muscle relaxants was the most frequently used method (1260 instances), followed by nitrous oxide sedation (163 instances) and sevoflurane GA with a laryngeal mask airway (158 instances). Inhalational GA with muscle relaxants had the longest average duration (2.78 h) and the highest DMF index (7.43), reflecting its use in more severe dental conditions. Gender analysis revealed a slight male predominance in using inhalational GA with muscle relaxants (55.87% male vs. 44.13% female). Female patients demonstrated higher follow-up compliance across all periods. Overall, our results highlight the importance of tailored anesthesia and sedation plans, as well as follow-up protocols, in pediatric dentistry. This study provides valuable insights for practitioners in selecting appropriate anesthesia and sedation types and developing strategies to improve follow-up compliance and treatment success.